Parental social position, in utero growth and risk of child development disorders: an administrative data based prospective cohort study: IJPDS (2017) Issue 1, Vol 1:222 Proceedings of the IPDLN Conference (August 2016) - Playford, Chris; Dibben, Chris; Williamson, Lee; Huang, Zengyi (International Journal of Population Data Science, 2017)
ABSTRACT Objectives To evaluate the influences of low birthweight and socioeconomic status upon child development disorders Approach It has been recognised that low birthweight and socio-economic status impact cognitive development in children. Previous studies in Scotland investigated this relationship using the Scottish Mental Health Survey 1932, the Growing Up in Scotland (GUS) longitudinal survey, and the Aberdeen Children of the 1950s study. This paper examines this using the Scottish Longitudinal Study (SLS) linked with Maternity Inpatient and Day Case records and Child Health Systems Programme Pre-School (CHSP Pre-School) records. This is original because it extends previous work through large-scale contemporary data which has been routinely collected and is representative of the Scottish population. It also includes a novel design through the use of birth data from parents and children recorded within the SLS. Results From this research it was identified that these child development measures were strongly associated with gestational-age specific birthweight and that fine motor, social and hearing abnormalities were much more likely for children with parents in lower grade occupations or who were long-term unemployed. These associations were net of other indicators of family socioeconomic position and birth outcomes, suggesting that infants from disadvantaged backgrounds remained more likely to experience these conditions beyond the differences that could be explained by other relevant factors (such as their birthweight). Conclusion These findings confirm and build upon previous analysis through the use of linked administrative data.